Mobile Technologies, Financial Inclusion, and Inclusive Growth in East Indonesia - Esquivias, Miguel Angel; Sugiharti, Lilik; Jayanti, Ari Dwi; Purwono, Rudi; Sethi, Narayan (Journal of Telecommunications and the Digital Economy, 2020)
This paper examines the influence of mobile technologies on financial inclusion, and the matter of whether mobile technologies and financial inclusion have an impact on the income of individuals in East Indonesia, considering the data from the Survey on Financial Inclusion and Access (SOFIA) in 2017. A seemingly unrelated probit model and an ordinary least-squares model are used to compare both determinants of formal and informal financial services, as well as simple and smart mobile technologies. The study finds that mobile technologies and access to finance significantly increase the likelihood of higher incomes. Smart technologies and formal finance have higher effects on incomes compared to the effects of simple devices or semi-formal and informal finance. Significant gaps in financial access exist between individuals in accordance with gender, income, education, and location. Technologies account for a small difference in the broader access to financial services.